10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
INTRODUCTION: Coronary artery bypass grafting (CABG) is one of the most common major surgical procedures, and patients often experience severe postoperative pain. Effective, safe, and nonpharmacological strategies are needed to support pain management and physiological stability after CABG. This study aimed to evaluate the effect of classical hand massage on postoperative pain and physiological parameters in patients undergoing CABG surgery. METHODS: This single-blind randomized controlled trial study was conducted with 80 patients in the cardiovascular surgery intensive care unit. The intervention group received 30 min of classic hand massage (15 min per hand) in addition to routine care, while the control group received routine care alone. The primary outcome was postoperative pain intensity measured using the Visual Analog Scale (VAS). Secondary outcomes included systolic blood pressure, diastolic blood pressure, pulse rate, respiratory rate, and oxygen saturation. These outcomes were assessed before the intervention (T0) and at 5, 30, 60, 90, and 120 min thereafter (T1-T5), and between-group differences were evaluated at a significance level of p < 0.05. RESULTS: Classic hand massage significantly reduced sternotomy pain at all follow-up times (2.30-3.50 vs. 5.37-6.20; p < 0.001). Drain pain was also lower at 5 min (2.07 ± 0.64 vs. 3.94 ± 1.25) and 30 min (2.07 ± 0.64 vs. 4.11 ± 1.32) (p < 0.001). Back and leg-incision pain showed no between-group differences (p > 0.05). Systolic blood pressure was lower at 30 and 60 min (p = 0.012; p = 0.037), and diastolic blood pressure at 5 and 30 min (p = 0.015; p = 0.018). Respiratory rate decreased and oxygen saturation increased at all times (p < 0.001). Pulse rate did not differ (p > 0.05). No patient requested analgesics. No adverse events or intervention-related harms were observed during the study period. CONCLUSION: Hand massage was associated with lower pain scores and favorable physiological responses in patients undergoing CABG surgery. Nevertheless, further multicenter studies with larger sample sizes are needed to strengthen the evidence base and support the generalizability of these findings.